New data on the level of immune stratum against Q fever agent in population of the of Republic of Guinea - E. V. Naydenova; S. Kalivogui; M. Yu. Kartashov; A. V. Boyko; S. Boumbaly; V. A. Safronov; K. S. Zakharov; A. A. Nassour; F. Drame; O. K. Konstantinov; N. F. Magassouba; M. A. Boiro; et al. (Инфекция и иммунитет, 2021)
which is bacteria of the species Coxiella burnetii. One of the factors showing the possibility of pathogen circulation in a certain territory is assessed by the presence of an immune stratum in the inhabitants of the region. In the 1980s, the study of the immune structure of the population of the Republic of Guinea in relation to coxiellosis has begun. The present study, carried out in 2015—2019, has been aimed to obtain new information about the immune stratum of the population of the Republic of Guinea against the causative agent of Q fever and to compare it with previous studies. Specific IgG antibodies in the blood of the Guinea residents were detected by using enzyme-linked immunosorbent assay (ELISA) with a set of reagents manufactured at the St. Petersburg Pasteur Institute (St. Petersburg, Russian Federation). The serum samples were tested in at 1:100 dilution. Antibodies against C. burnetii were detected in 124/2346 (5.3% [CI 4.5-6.3]) samples. This study confirms the previously obtained data on the circulation of the causative agent of coxiellosis in all landscape and geographical zones of the Republic of Guinea. The natural and climatic conditions of the region, the variety of ixodic tick species currently inhabiting this territory being a reservoir and vector of infection, as well as a large amount of livestock are the factors for active circulation of the Q fever pathogen and the emergence of related disease outbreaks. The data obtained necessitate continuing further studies on distribution of C. burnetii in the territory of the Republic of Guinea. Taking into consideration the epidemiological significance of Q fever, a pressing task is to study a proportion of this infectious disease in the overall structure of diseases registered in the territory of the Republic of Guinea. It is also necessary to conduct regular epizootological monitoring in order to clarify the types of carriers and vectors of C. burnetii in different landscape and geographical zones of the Republic of Guinea as well as to assess the immune stratum against the pathogen in large and small cattle being the main sources of infection for humans. The data obtained will allow us to determine presence of a natural focus of this infection as well as its borders and develop a set of preventive (anti-epidemic) measures.